Analysis Of The Preservation Of The Watershed As Well As The Settings In The Regulations - Irhamna Mandily Lubis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Watershed hereinafter referred to as watershed is an area of land that is in unity with the river and its tributaries, which serves to accommodate, save and drain the water derived from precipitation to the lake or to the sea naturally, a limit on the land is a separator topographic and boundary in the ocean up to the water that still affected the activity of the mainland. So necessary to the preservation of watershed management and the presence of laws and regulations that govern them. This is necessary because the area of flow of the river can provide considerable benefits to the keberlangsunga of human life such as spared from the flood, and can utilize the river water for daily needs as well as other benefits. The settings on the management of the flow of the river is regulated in government regulation No. 37 of 2012 as well as the LAW Number 32 Year 2009 on environmental protection and management. Thus also against the sanctions for violation of the watershed is necessary because in order to achieve the preservation of the watershed itself. Regarding sanctions on violations of the watershed is in the form of criminal sanctions of imprisonment and a fine as stipulated in LAW No. 32 Year 2009 whereas in the Permenhut No. 87/Menhut-II/2014 On Guidelines for Planting For the Holder of The Permit In Order watershed Rehabilitation only provide administrative sanctions against violators.